Movement of Hindu Religious Education in The Era of The Kingdom of Majapahit - Marsono; Rahayu, Ni Wayan Sri (Institute for Advanced Science, Social, and Sustainable Future, 2023)
The history of the Hindu-Buddhist Kingdoms in the Archipelago does not only talk about politics but also about civilization and efforts to improve education. Education is a human need since ancient times. Leaders from various eras attempted to build Educational centers to educate citizens. During the time of the kingdoms in the archipelago, educational centers had been built to develop superior human resources. Majapahit was a large empire in the archipelago that was able to survive for several centuries. As a large empire, Majapahit has a good education system with its institution called mandala kadewaguruan (Education Center). Kadewaguruan is led by a mahāresi who is also called śiddharesi, dewaguru, therefore this education center is called Kadewaguruan. Based on information from various texts, the identifying elements of a religious education center (mandala kadewaguruan ) are: (1) a large place; (2) pottery-ceramics were found; (3) various religious artifacts were found; (4) away from the crowds; and (5) reported in the text. Mandala Kadewaguruan as an educational institution in the Majapahit era divides the education stage into 2 stages, which are called the preparatory stage and the core stage. The article examines in more depth the Hindu education center in the Majapahit era by conducting field research, analyzing research, documents and texts related to Hindu education in the Majapahit era. In this era, education is carried out comprehensively with learning taking place throughout the day. Students can learn various values of life in addition to learning according to the level taught.